1996
DOI: 10.1046/j.1365-2559.1996.262303.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary signet‐ring cell carcinoma of the urinary bladder

Abstract: Primary signet-ring cell carcinoma of the urinary bladder Signet-ring cell carcinoma of the urinary bladder is a rare tumour, accounting for approximately 0,24% of all bladder malignancies. In this study, the clinicopathological findings in 13 cases are described. This malignancy is far more common in men than in women (ratio 11:2). The distribution by age and clinical symptoms can not distinguish it from transitional cell carcinoma. The tumour behaves like other high grade malignancies, presenting frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 30 publications
0
32
1
Order By: Relevance
“…This appears related to a linitis plastic-like growth pattern rendering cystoscopic detection difficult and the outlook poor. 7 Adeno-or signet-ring cell carcinomas identified in the bladder are rare entities and may represent metastases from other primary sites, usually from the gastrointestinal tract. Clinical imaging and immunohistochemical findings in our patient were compatible with the primary source of signet cell cancer arising from the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…This appears related to a linitis plastic-like growth pattern rendering cystoscopic detection difficult and the outlook poor. 7 Adeno-or signet-ring cell carcinomas identified in the bladder are rare entities and may represent metastases from other primary sites, usually from the gastrointestinal tract. Clinical imaging and immunohistochemical findings in our patient were compatible with the primary source of signet cell cancer arising from the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…9 In the recent WHO classification of urinary system tumor (2004), infiltrative urothelial carcinoma with a component Pure signet-ring cells carcinoma is a highly malignant deep-infiltrating tumor with a very poor outcome. 14 The real content of the vacuoles in the cytoplasm of lipoid cells remains uncertain. Borzacchiello et al 3 have reported a case of lipid-cell variant of urothelial carcinoma of the urinary bladder in a cow.…”
Section: Discussionmentioning
confidence: 99%
“…Such adenocarcinomas are thought to arise from totipotent cells of the transitional epithelium or from the remnants of the cloaca. [5]…”
Section: Discussionmentioning
confidence: 99%